Optical and structural characteristics of PMMA films doped with a new anisometric EuIII complex. Issue 4 (14th June 2019) - Knyazev, Andrey; Krupin, Aleksandr; Gubaidullin, Aidar; Galyametdinov, Yury
Abstract : A new film material capable of transforming UV radiation into visible light was obtained from a new Eu III anisometric complex with organic ligands in a polymethylmethacrylate (PMMA) matrix and structurally characterized. From X‐ray powder diffraction and small‐angle scattering data, it is supposed that molecules of the Eu III complex occur in the voids of the PMMA matrix and this is accompanied by the formation of a nanocrystalline phase. Abstract : A new film material capable of transforming UV radiation into visible light was obtained from a highly anisometric Eu III complex with organic ligands in a polymethylmethacrylate (PMMA) matrix and then structurally characterized. An important advantage of the synthesized complex is its good solubility in organic solvents such as dichloromethane, chloroform, THF, toluene, etc . The ligand environment (flexible alkyl and cyclohexyl substituents) of the Eu III complex was selected to prevent crystallization, to inhibit the formation of defects in the structure of films and to provide its uniform distribution in the polymer during polymerization. As a result we obtain an Eu III complex of the film with remarkable thermal behavior: the complex melts to isotropic liquid without decomposition, it supercools at ambient temperature and it forms a stable amorphous material at low (up to −30°C) temperatures. The films were prepared by two methods: bulk polymerization and spin coating. A comparison of the differences of luminescent and optical characteristics of micro‐ and nanosized PMMA films doped with the anisometric Eu III complex is given. Based on X‐ray powder diffraction and small‐angle scattering data, it has been supposed that the association of Eu III complex molecules occurs in the voids of the PMMA matrix and is accompanied by the formation of a nanocrystalline phase. For films obtained by spin coating, a deeper microphase separation is demonstrated than by bulk polymerization. The dimensional characteristics of the nano‐associates were determined and a correlation between the method of preparation and the type of distribution of the Eu III complex in the PMMA matrix is established.